2016
DOI: 10.23910/ijbsm/2016.7.2.1423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bagging on Fruit Quality of Guava

Abstract: An investigation on improvement of quality of guava cv. Lalit fruits through bagging was carried out at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 3 publications
4
10
1
Order By: Relevance
“…1). The results coincided with the findings of Meena et al (2016). They found the highest vitamin-C content (171.14 mg 100g −1 ) under white poly bag.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…1). The results coincided with the findings of Meena et al (2016). They found the highest vitamin-C content (171.14 mg 100g −1 ) under white poly bag.…”
Section: Discussionsupporting
confidence: 90%
“…These might be attributed due to different treatments and sunlight. Such results partially supported by the findings of Meena et al (2016). They reported that maximum TSS content was found in yellow polythene bag (30.07%) and the minimum was in control condition (14.46%).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Besides insect control, bagging also influences the post-harvest and quality of the fruit, and may even increase weight, modify fruit color (Tokairin et al, 2014), as well as increase size, humidity, and the contents of vitamin C (Hossain et al, 2018) and soluble solids (Edirimanna et al, 2015;Meena et al, 2016).…”
Section: Introductionmentioning
confidence: 99%